The effect of interference of corrosion pits on the failure probability of a reinforced concrete beam. (1st May 2016) - Kioumarsi, Mahdi M.; Hendriks, Max A.N.; Kohler, Jochen; Geiker, Mette R.
Highlights: We calculated the probability of failure of a corroded reinforced concrete beam. The interference of corrosion pits in adjacent rebars has been modelled explicitly. The spacing of corrosion pits is represented by a Poisson process. Abstract: Assuming given corrosion states this paper studies the effect of interference of corrosion pits on adjacent rebars on the probability of bending failure of a corroded reinforced concrete beam. Spatial distribution of localised corrosion along a beam is considered in the analyses. The probability of failure is estimated using Monte Carlo simulation. Uncertainties in material properties, geometry, loads, and corrosion damage are taken into account. Statistical data for the extent and location of corrosion is taken from literature and utilized in order to calibrate parameters of corresponding probability distribution functions. Results show that considering possible interference of localised corrosion has substantial influence on the estimated probability of failure. The results are compared with results from two practical methods which appeared not always to be conservative.